A 27-year-old Man with Chronic Kidney Disease and Intradialytic Hypertension, A Review of Psychological Aspects as Risk Factors - Wiraanjani, Belinda; Nyoman Desy Lestari, Desak (Greenation Publisher & Yayasan Global Research National, 2025)
Intradialytic Hypertension (IDH) is a complication that can occur in patients with chronic kidney disease (CKD) undergoing hemodialysis, with a prevalence of 5% to 15%. Intradialytic hypertension can be caused by various factors, including fluid overload, sympathetic overactivity, activation of the renin-angiotensin-aldosterone system (RAAS), endothelial dysfunction, elevated sodium levels, medications such as erythropoietin, and vascular stiffness. Case report : A 27-year-old male patient (KNW) with CKD and intradialytic hypertension was evaluated to determine the underlying cause of his condition. Discussion : A detailed analysis was conducted to assess potential contributing factors, including an underlying disease or other risk factors such as a hereditary predisposition from the patient’s father, as well as anxiety, stress, and depression, along with lifestyle factors such as heavy smoking, alcohol consumption, and lack of exercise awareness. The patient was subsequently provided with both non-pharmacological and pharmacological therapies. Educational counseling was offered regarding dietary and fluid intake, exercise, adherence to hemodialysis (HD) sessions, and the importance of medication compliance. Conclusion : Following this intervention, improvements were noted, including the resolution of headaches and stabilization of blood pressure. The likely contributing factors for this patient's intradialytic hypertension were psychological issues, poor medication adherence, and a lack of social support. The management strategy successfully achieved target blood pressure levels, thereby preventing further complications related to intradialytic hypertension.